2014
DOI: 10.1101/gad.244368.114
|View full text |Cite
|
Sign up to set email alerts
|

CDK9-mediated transcription elongation is required for MYC addiction in hepatocellular carcinoma

Abstract: One-year survival rates for newly diagnosed hepatocellular carcinoma (HCC) are <50%, and unresectable HCC carries a dismal prognosis owing to its aggressiveness and the undruggable nature of its main genetic drivers. By screening a custom library of shRNAs directed toward known drug targets in a genetically defined Myc-driven HCC model, we identified cyclin-dependent kinase 9 (Cdk9) as required for disease maintenance. Pharmacological or shRNA-mediated CDK9 inhibition led to robust anti-tumor effects that corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
192
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(204 citation statements)
references
References 71 publications
(99 reference statements)
10
192
2
Order By: Relevance
“…Human PDAC cells as well as autochthonous PDAC models indicate that BET inhibition also provokes MYC down-regulation and suppression of pancreatic tumorigenesis in conjunction with HDAC inhibition (Mazur et al 2015). The attractiveness of MYC as a target also stems from the observation that MYC binds to promoter regions of active genes and causes transcriptional "amplification" (Lin et al 2012;Nie et al 2012), which appears to engender vulnerability to blockade of transcriptional elongation by targeting CDK9, a key component of the transcription elongation complex (Huang et al 2014). Interestingly, a recent study showed that suppression of MYC results in induction of PGC1α and increased mitochondrial respiration, which functions to sustain the PDAC CSC population, implicating the utility of targeting mitochondria oxidative phosphorylation (OXPHOS) in combination with MYC inhibition (Sancho et al 2015).…”
Section: Additional Amplified Oncogenesmentioning
confidence: 99%
“…Human PDAC cells as well as autochthonous PDAC models indicate that BET inhibition also provokes MYC down-regulation and suppression of pancreatic tumorigenesis in conjunction with HDAC inhibition (Mazur et al 2015). The attractiveness of MYC as a target also stems from the observation that MYC binds to promoter regions of active genes and causes transcriptional "amplification" (Lin et al 2012;Nie et al 2012), which appears to engender vulnerability to blockade of transcriptional elongation by targeting CDK9, a key component of the transcription elongation complex (Huang et al 2014). Interestingly, a recent study showed that suppression of MYC results in induction of PGC1α and increased mitochondrial respiration, which functions to sustain the PDAC CSC population, implicating the utility of targeting mitochondria oxidative phosphorylation (OXPHOS) in combination with MYC inhibition (Sancho et al 2015).…”
Section: Additional Amplified Oncogenesmentioning
confidence: 99%
“…A recent RNA interference screen in a MYC-driven hepatocellular carcinoma found CDK9 as a target and showed that CDK9 inhibitors blocked proliferation of MYC-amplified tumors (25). Treatment of mixed-lineage leukemias with CDK9 inhibitors reduced MYC expression (26), suggesting that MYC is a target of CDK9-mediated transcriptional control.…”
Section: Cdk9 Targeting Decreases Btic Growth and Self-renewalmentioning
confidence: 99%
“…Depending on tissue-specific signaling pathways, CDK9 responds to cytokines, including the tumor necrosis factor and interleukin-6 (MacLachlan et al 1998, Bellan et al 2004. Studies on different human cancers like lymphoma (Bettayeb et al 2007, Gregory et al 2015, neuroblastoma (De Falco et al 2005), PCa and several instances of hematopoietic malignancies (Huang et al 2014) revealed that CDK9-related pathways are deregulated, indicating that CDK9 hyperactivity may promote the expression of anti-apoptotic factors and induce proliferation (Jin et al 2015). Even though CDK9 has a crucial role in both normal and cancer cells, overexpression of short half-lived anti-apoptotic factors like MCL-1, BCL-2 and Figure 1 Regulation of transcription by CDK9.…”
Section: Biology Of Cdk9mentioning
confidence: 99%